C2TP: a service model for cloud. (1st January 2011) - Peiris, Chris; Sharma, Dharmendra; Balachandran, Bala
The notion of cloud computing capability is gathering momentum rapidly. However, the governance and enterprise architecture to obtain repeatable, scalable and secure business outcomes from cloud computing is still greatly undefined. There is very little research explored to define a framework that not only considers financial motivations, but also business initiatives, IT governance structures, IT operational control structures and technical architecture requirements to evaluate the benefits regarding cloud investment. We are proposing a novel model to address this. This model can be leveraged by an organisation to evaluate the 'tipping point' where the organisation can make an informative decision to embrace cloud computing at the expense of on-premise hosting options. The authors refer to this model as cloud computing tipping point (C2TP) model. The model is a service centric framework created by mapping cloud computing attributes with industry best practices such as ValIT, COBIT and ITIL.